Couldn’t Be Happier: The Non-Identity Intuition and Valuing People - Fischer, Jessica J. T. (Journal of moral philosophy, 2025)
This paper raises a worry about the non-identity intuition. As one part of the non-identity problem, the non-identity intuition tells us that when choosing between bringing a person with a good life into existence and bringing a person with a great life into existence, we have moral reason to bring the person with a great life into existence. But there is a worry to be had about the non-identity intuition. Because the non-identity intuition compares future persons exclusively in regard to their well-being, the non-identity intuition values future persons solely for the well-being enjoyed by each of them. Therefore, or so the worry goes, the non-identity intuition fails to be compatible with what it means to value persons for their own sake.